Influence of IL-1β, STAT3 & 5 and TLR-5 gene polymorphisms on rheumatic heart disease susceptibility in north Indian population. (15th September 2019) - Bhatt, Mansi; Kumar, Surendra; Garg, Naveen; Siddiqui, Mohammad Haris; Mittal, Balraj
Abstract: Background: Rheumatic heart disease (RHD) is the most serious complication of heart that comprises inflammatory reactions in heart valves. Many studies have demonstrated the contribution of host genetic factors in susceptibility to RHD and many cytokine gene variants have been linked with susceptibility to RHD. We sought to determine the role of genetic variants in IL-1β, STAT3, STAT5B and TLR5 genes in conferring risk of RHD in two cohorts of RHD patients. Methods: The study included 400 echocardiography confirmed RHD patients and 300 controls from North Indian Population. We categorized RHD patients into two sub-groups based on involvement of heart valves, mitral valve lesion alone (MVL), and combined valve lesions including mitral valve (CVL). Genotyping for all the polymorphisms was done using TaqMan /PCR-RFLP methods. Results: Our results showed that the genotypic frequencies of IL-1β, STAT3, STAT5B andTLR5 genes polymorphisms were significantly associated with RHD risk. To validate our results, we performed a replication study in additional 200 cases with similar clinical characteristics and results again confirmed consistent findings with RHD risk. In subgroup analysis, STAT3 polymorphism remained significant with MVL in RHD patients. Conclusion: IL-1β, STAT3, STAT5B and TLR5 genes polymorphism may be useful markers for the identification of individuals with high risk of RHD in the susceptible population. Highlights: IL-1β, STAT3, TLR5 gene polymorphism affect risk of rheumatic heart disease (RHD). STAT3 variant associates with higher risk of mitral-valve disease in RHD patients. These genetic variants may be useful biomarkers for RHD in susceptible population.